Psychosocial Profile Of Spanish And Portuguese Family Preservation Users: An Analysis Of Needs And Intervention Clues - Ayala-Nunes, Lara; García, Maria Victoria Hidalgo; Jiménez, Lucía; de Jesus, Saul Neves (Journal of Tourism, Sustainability and Well-being, 2016)
At-risk families live under circumstances that hinder their parenting competences, compromising their ability to fulfill their children’s needs appropriately. The complex and multiple-source nature of the adversities that they endure makes family preservation interventions challenging. Because their efficacy largely depends on the extent to which interventions fit participants’ needs and characteristics, the aims of this study were to draw the sociodemographic (individual, family, economic, labor, and child-related variables) and psychosocial profile (negative life events, parenting stress, and psychological distress symptomatology) of Spanish and Portuguese family preservation users while testing the inter-country differences. The results showed that the majority of participants had a low educational level, were unemployed, and were poor. Spanish and Portuguese participants had suffered an average of 5 and 4 negative life events over the past 3 years, respectively, with a high emotional impact. The most common were labor precariousness and economic hardship. Clinical levels of parenting stress were found in 48.1% of the Spanish participants and 39.1% of the Portuguese participants. An important proportion of the participants had clinical levels of psychological distress (Spain = 71.9%; Portugal = 45.8%), indicating the presence of mental health problems. Families’ support needs are discussed and guidelines for interventions aimed at improving parents’ and children’s well-being are outlined.